Natriuretic Peptides in Hypertension and Related Disorders - Pandey, Kailash N. (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Atrial and brain natriuretic peptides (ANP and BNP) belong to a family of related hormones, which exhibit natriuretic, diuretic, and vasorelaxant activities and play pivotal role in renal, cardiovascular, and endocrine homeostasis. The investigations on ANP and BNP have produced a huge body of important information, which have helped to increase our understanding of the control of high blood pressure (BP), renal and cardiovascular disorders, and recently energy metabolism and fat oxidation. Interestingly BNP and its N-terminal fragment (NT-proBNP) are greatly increased in the circulation of heart failure (HF) patients, and thus considered the excellent predictors of heart disease. In particular, NT-proBNP often found to be gold standard marker of HF. The spectrum of studies, including biochemical, molecular, genomic, and clinical investigations have helped to delineate the roles of natriuretic peptides (NPs) and their receptors in the signaling mechanisms of a wide range of physiological functions. The gene-targeting and transgenic animal models have further heightened our understanding of the importance of NPs and their cognate receptors in both physiological and pathophysiological milieu and disease conditions. This chapter describes the salient features and the roles of NPs and their receptors in hypertension and cardiovascular diseases. Indeed, more investigations are needed to extend the function of NPs in these important areas of research to enhance the clinical benefits to human population.